“The Dilemma of Democracy in Public Service Broadcasting.” Comparison of the BBC and RÚV Pre-Election Coverage Frameworks - Vera Dagsdóttir 1989- (2013)
In this dissertation the pre-election coverage frameworks of two public service broadcasters, the BBC in the United Kingdom and RÚV in Iceland, will be compared. The aim is to evaluate whether criticism against RÚV’s pre-election coverage and subsequent reform proposals aim to bring RÚV closer to the BBC’s current pre-election coverage framework. Although both are public service broadcasters, the different environments in which they operate influence their frameworks. In the theoretical framework, relevant democratic theories in relation the public service broadcasters will be discussed: the social contract theory, deliberative democracy and the public sphere. Subsequently, the BBC’s pre-election coverage framework is addressed, which comprises Party Election Broadcasts (PEBs) and the impartiality rule, with arguments for and against it. In this context, the relative merits of the BBC's coverage will be examined. A report from the Organisation for Security and Co-operation in Europe (OSCE) focusing on the lack of rules governing RÚV’s current pre-election coverage framework and a newly proposed law for the public broadcaster, which proposes pre-election coverage rules, are discussed. Given this context, the factors controlling RÚV’s pre-election coverage in the absence of a regulatory framework are examined. The main conclusions are that criticism and proposed reforms of RÚV are leading it to conform with the BBC’s current framework. The media and their political environments do, however, contribute to their differences and demonstrate that there is not one single model that can be adapted for every pre-election coverage framework. Í þessari ritgerð verður tekinn fyrir samanburður á umfjöllunarramma tveggja opinberra ljósvakamiðla í aðdraganda kosninga, BBC í Bretlandi og RÚV á Íslandi. Markmiðið er að meta hvort gagnrýni á núverandi umfjöllunarramma RÚV í aðdraganda kosninga og umbótartillögur miði að því að færa RÚV nær umfjöllunarramma BBC. Færð verða rök fyrir því að þessir opinberu ljósvakamiðlar deili ...